Hubungan Dukungan Suami Terhadap Pelaksanaan Inisiasi Menyusu Dini - Nidya Aryani; Jupri Kartono (LPPM STIKes Panca Bhakti Bandar Lampung, 2021)
Early Initiation of Breastfeeding is a breastfeeding process that starts as soon as possible which is done by allowing the baby to have skin contact with the mother's skin for at least the first hour after birth or until the early breastfeeding process ends. Husband's support plays a role in the implementation Early Initiation of Breastfeeding where many husbands are found who do not support or motivate because they do not know or understand about Early Initiation of Breastfeeding. Aim to determine the relationship between husband's support and the implementationEarly Initiation of Breastfeeding in post partum mothers at the Independent Midwife Practice. The type of research used is quantitative with a cross sectional research design. The population of this study were all spontaneous postpartum mothers who were accompanied by their husbands during childbirth at the Independent Midwife Practice Bandar Lampung during June-August 2019 as many as 33 people. The research sample used accidental sampling method, namely the entire population as a sample. Questionnaires are used as a tool for data collection. The data analysis used was Chi-square bivariate analysis. Results based on the results of the study, 84.8% (28 people) succeeded in doing Early Initiation of Breastfeeding and 78.8% (26 people) who received the support of their husbands to do Early Initiation of Breastfeeding. The results of statistical tests with chi square obtained p-value = 0.004 and OR = 33.333. Conclusion There is a relationship between husband's support for the implementation Early Initiation of Breastfeeding in maternity mothers at the Independent Midwife Practice in 2019. Suggestions for midwives as the spearhead of service to be more active in providing counseling, especially on antenatal checks by providing education about Early Initiation of Breastfeeding program not only to mothers but also to husbands so that they understand the benefits and importance so as to support the implementation Early Initiation of Breastfeeding during childbirth.